Novejši urbarji za Slovenijo 2 Urbarji belopeškega gospostva - Mlinar, Janez (Thesaurus memoriae, 2018)
The Bela Peč (Weißenfels) dominion, which encompassed with the exception of the Dovje (Lengenfeld) and Koroška Bela (Kärntner Vellach) the entire area of the Upper Sava Valley, was formed as an independent economic and administrative unit in the middle of the 15th century. The living of the dominion was defined especially by the Alpine world with specific climatic conditions and extensive iron ore deposits. The book contains the edition of two oldest domain urbarium from 1498 and 1636, which offer an excellent economic, demographic and social image of domain, where agrarian and non-agrarian production intensively intertwine. As such it is an interesting starting point for possible further comparative studies not only for the area of present-day Slovenia, but also for the wider eastern Alpine region and Friuli. The edition is accompanied by an extensive study.